The Role of Legal Empowerment Based Advocacy for Rural Communities on Structural Social Inequality - Tama, Rifqi Anugrah; Ikrom, Mohamad; Dixon, Edward; Nte, Ngaboawaji Daniel; Idris, Siti Hafsyah (Faculty of Law, Universitas Negeri Semarang, 2023)
Indonesia is a portrait of a legal state, the rights of the people have been protected by the Constitution, contained in the 1945 Constitution of the Republic of Indonesia. Substantially regarding advocacy assistance to the community is regulated in Article 28 of the Constitution of the Republic of Indonesia